Solutions of systems of nonlinear difference-differential equations of neutral type asymptotically bounded in the entire axis - Pelyukh, G. P.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For a certain class of systems of difference-differential equations of neutral type, we study the properties of solutions asymptotically bounded on the entire axis.